Exercise Influence on Hippocampal Function: Possible Involvement of Orexin-A - Chieffi, Sergio; Messina, Giovanni; Villano, Ines; Messina, Antonietta; Esposito, Maria; Monda, Vincenzo; Valenzano, Anna; Moscatelli, Fiorenzo; Esposito, Teresa; Carotenuto, Marco; Viggiano, Andrea; Cibelli, Giuseppe; et al. (Frontiers in Physiology, 2017)
In the present article, we provide a brief review of current knowledge regarding the effects induced by physical exercise on hippocampus. Research involving animals and humans supports the view that physical exercise, enhancing hippocampal neurogenesis and function, improves cognition, and regulates mood. These beneficial effects depend on the contribute of more factors including the enhancement of vascularization and upregulation of growth factors. Among these, the BDNF seems to play a significant role. Another putative factor that might contribute to beneficial effects of exercise is the orexin-A. In support of this hypothesis there are the following observations: (1) orexin-A enhances hippocampal neurogenesis and function and (2) the levels of orexin-A increase with physical exercise. The beneficial effects of exercise may represent an important resource to hinder the cognitive decline associated with the aging-related hippocampal deterioration and ameliorate depressive symptoms.